2020
DOI: 10.1016/j.celrep.2020.107699
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Triggers a Dynamic Sequence of Transient Microglial Alterations in Juvenile Brain

Abstract: Highlights d Irradiation (IR) triggers transient microglial activation in the hippocampus d Microglia undergo a series of temporally regulated transcriptomic changes after IR d Single-cell RNA-seq reveals heterogeneous microglial populations after IR d Microglia upregulate pro-and anti-inflammatory genes simultaneously after IR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 94 publications
1
35
0
1
Order By: Relevance
“…Although the Warburg effect was first described in cancer cells, immune cells may also undergo glycolytic reprogramming [ 10 , 11 ]. Microglia cells, as resident macrophages, are triggered by irradiation [ 27 ]. Different degrees of dependance on glycolysis or oxidative phosphorylation lead to different degrees of polarization of microglia cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Warburg effect was first described in cancer cells, immune cells may also undergo glycolytic reprogramming [ 10 , 11 ]. Microglia cells, as resident macrophages, are triggered by irradiation [ 27 ]. Different degrees of dependance on glycolysis or oxidative phosphorylation lead to different degrees of polarization of microglia cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell and animal research continue to help bridge the gap in areas which human studies cannot explore. Various studies have shown a range of microglial responses to high dose ionising radiation; notably that irradiation using a high dosage will elicit a neuroinflammatory response [18,[114][115][116][117][118]. A dose of 0.5 Gy has been shown to increase the number of microglia in the hippocampus, compared to control and low dose ionising radiation (0.063 Gy); however, the microglia were less ramified than before [118].…”
Section: Impact Of Ionising Radiation On Healthy Brains By Altering Microglial Function Statesmentioning
confidence: 99%
“…Microglia, the resident immune cells of the central nervous system (CNS), respond to external stressors such as pathogenic invasion and injury by inducing inflammation [16][17][18]. During microglial activation, microglia are polarised from the M2 anti-inflammatory state to the M1 pro-inflammatory state [16,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple progenitor cell populations are now known to reside in the adult human brain 34. Injury to the mammalian brain can trigger a tightly orchestrated, dynamic response that involves many cell types, including microglia, astrocytes, and endogenous neural progenitors 56. Genetic tools to inhibit innate responses may exacerbate the resultant damage 7.…”
Section: Introductionmentioning
confidence: 99%